Enhance 1,3-propanediol production from crude glycerol in batch and fed-batch fermentation with two-phase pH-controlled strategy - Sattayasamitsathit,Supalak (Pontificia Universidad Católica de Valparaíso, 2011)
The batch fermentation of 1,3-propanediol (1,3-PD) by Klebsiella pneumoniae SU6 at different crude glycerol concentration (40-100 g l-1), pH (6.5-7.5) and temperature (31-40ºC) combined with two-phase pH-controlled strategy was investigated. Effect of feeding rate (0.10-0.15 L h-1) was studied in fed-batch fermentation. In batch fermentation, the optimal condition was 60 g l-1 crude glycerol, pH control at 6.5 and cultivation temperature at 37ºC. The maximum 1,3-PD of 20 g l-1, the yield of 0.34 g 1,3-PD g-1 glycerol consumed and the productivity of 1.25 g l-1 h-1 were achieved at 16 hrs cultivation. The by-products were acetic acid and succinic acid at 2.7 and 1.1 g l-1, respectively. Two-phase pH-controlled strategy gave better results (24.95 g l-1 1,3-PD and 1.78 g l-1 h-1 productivity) than constant pH-controlled strategy (20 g l-1 and 1.25 g l-1 h-1, respectively) at 16 hrs incubation. In fed-batch fermentation, the maximum 1,3-PD of 45.35 g l-1 was achieved at constant feeding rate of 0.1 L h-1. The yield and productivity were 0.44 g g-1 and 1.94 g l-1 h-1, respectively. The fed-batch fermentation with constant feeding at 0.1 L h-1 with two-phase pH-controlled strategy gave 2.2 folds higher 1,3 PD concentration than the batch fermentation with two-phase pH-controlled strategy. This demonstrated the great impact of combination of pH control and feeding strategies in fed-batch fermentation on enhancing 1,3-propanediol production.